Diagnosing the Actual Reality of the Requirements of Ecological Design According to ISO14006:2020: A Case Study in Engineering Reconstruction Office-Iraq - Zainab Mahdi Muhammad; Areej Saeed Khalil (Journal of Techniques)
The research aims to identify the extent of the commitment of the Department of Engineering Reconstruction to the application of ecological design according to the guiding specification ISO14006:2020 by measuring and diagnosing the gap between the actual reality in the Department of Engineering Reconstruction and the requirements of the specification, and to achieve this goal, the case study approach was adopted, and the checklist was adopted to measure the gap.